Overexpression of DJ-1 correlates with aggressive clinicopathological characteristics and poor prognosis in malignant tumors: a meta-analysis - Wang, Qingting (Onco Targets Ther, 2018)
PURPOSE: A number of studies have investigated the role of DJ-1 in the development and progression of malignant tumors. This meta-analysis aims to systematically estimate the rela-tionship between the expression level of DJ-1 and the malignant biological behaviors of tumors and to assess the clinical significances of DJ-1 in the prognosis and diagnosis of cancer. MATERIALS AND METHODS: We searched PubMed, Web of Science, China National Knowledge Infrastructure and Wanfang databases from inception to December 1, 2017. Pooled odds ratio (OR) and hazard ratio (HR) with their 95% confidence interval and the diagnostic value of DJ-1 were calculated. RESULTS: Fourteen eligible studies with a total of 1,947 subjects were enrolled in our meta-analysis. The results showed that DJ-1 was overexpressed in cancer patients compared with noncancer patients (OR = 30.72), and elevated expression of DJ-1 was demonstrated to be closely associated with high tumor-node-metastasis stage (OR = 5.52), poor differentiated degree (OR = 2.46), positive lymph node metastasis (OR = 4.12) and worse overall survival (HR = 2.23). In addition, the combined sensitivity and specificity for DJ-1 to discern malignant tumors were 0.73 and 0.93, respectively. The diagnostic OR was 34.87, and the area under the summary receiver operating characteristic curve was 0.88. CONCLUSION: This meta-analysis demonstrated that DJ-1 was an important biomarker in tumor assessment and prognosis prediction.